2009
DOI: 10.1002/ar.20970
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Tolerance: The Mechanisms of Neuroprotective Strategy

Abstract: The phenomenon of ischemic tolerance perfectly describes this quote ''What does not kill you makes you stronger.'' Ischemic pre-or postconditioning is actually the strongest known procedure to prevent or reverse neurodegeneration. It works specifically in sensitive vulnerable neuronal populations, which are represented by pyramidal neurons in the hippocampal CA1 region. However, tolerance is effective in other brain cell populations as well. Although, its nomenclature is ''ischemic'' tolerance, the tolerant ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 87 publications
(122 reference statements)
1
67
0
1
Order By: Relevance
“…The concept of IPC is defined as a brief, non-injurious episode of ischemia, which can protect the brain cells from a subsequent longer ischemic insult (10,11). The first description of IPC in the brain was reported in a study by Kitagawa et al (30) in a gerbil model of global ischemia.…”
Section: Time Following Ischemia-reperfusion ------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of IPC is defined as a brief, non-injurious episode of ischemia, which can protect the brain cells from a subsequent longer ischemic insult (10,11). The first description of IPC in the brain was reported in a study by Kitagawa et al (30) in a gerbil model of global ischemia.…”
Section: Time Following Ischemia-reperfusion ------------------------mentioning
confidence: 99%
“…However, the exact mechanisms underlying neuronal damage in ischemia and delayed neuronal death remain to be fully elucidated. Ischemic preconditioning (IPC) represents an important adaptation of the central nervous system to sub-lethal ischemia, which results in an increased tolerance to ischemia in the central nervous system to a subsequent longer or lethal period of ischemia (10,11). IPC induces the expression of a diverse family of genes involved in cytoprotection, which, in turn, encode proteins that enhance brain resistance to ischemia (12).…”
Section: Introductionmentioning
confidence: 99%
“…A series of papers (Urban et al, 2009;Lehotsky et al, 2009b;Pavlikova et al,2009) found that ischemia/reperfusion injury (IRI) initiates time dependent differences in endoplasmic reticular gene expression at both the mRNA and protein levels in rat hippocampus and that endoplasmic gene expression is affected by pre-ischemic treatment. More recently, Pavlikova et al (2011) conducted an investigation into the differences between naive control and hyperhomocysteinemic control animals in each group independently.…”
Section: Effect Of Hyperhomocysteinemia On Spca Expressionmentioning
confidence: 99%
“…This leads to the trigger of the neuroprotective tolerance state. A number of common mechanisms with different relevance features can be recognized (Lehotsky et al, 2009b): -depression of metabolic rate, -modulation of glycolytic enzymes, -reduction of ion channel fluxes, -suppression of neural activity, -expression of chaperones and heat shock proteins (Hsp), -activation of antioxidant defense systems, -adaptation of blood rheology and others. At first pass, the patient population that suffers from cerebral ischemic injury due to unpredictable focal stroke, cardiac arrest, or subarachnoid hemorrhage represents, by definition, one that is unlikely to derive benefit from preconditioning research.…”
mentioning
confidence: 99%
See 1 more Smart Citation